Design and development of an online robot programming and simulation framework using the Robot Operating System (ROS) - Yap, Hwa Jen; Yeoh, Ru Sern; Tan, Chee Hau; Sivadas, Chandra Sekaran; Chang, Siow Wee; Liew, Kan Ern (2019)
In the Fourth Industrial Revolution, robotics technology plays an increasingly important role in order to increase productivity through the use of cyber-physical systems. However, industrial robotic arms require expertise in fields such as mechanical and software engineering in order to be used. Furthermore, the modularity of robotic work cells could be improved. In this project, an online robot programming and Simulation framework is developed in the Robot Operating System (ROS). The framework includes a master and slave node that allows for teleoperation of the intended robotic arm. A graphical user interface (GUI) is provided on the master personal computer (PC) in order to receive a target coordinate point for the robotic arm end-effector from the user. The EezyBotArm Mk2 3-dimensional (3D) printed arm is used for control and testing. The kinematics study of the robotic arm is performed and based on the equations derived is used to convert the coordinate point into the corresponding joint variables. The joint variables are then transmitted from the master PC to the slave Raspberry Pi. The Raspberry Pi interfaces with an Arduino UNO board in order to control the servo motors on the robotic arm via pulse width modulation (PWM) signal.